Design of thermoforming process for PETG part - Nur Anis Arina, Mokhzan (2016)
This project focuses on the drape forming process. The process involves draping a hot plastic sheet over a mold of the desired shape and allows the plastic to cool and harden to take shape. Aluminum of mold had been designed by using computer-aided design and simulated in CATIA V5R21 software. Venting line act as an air flow during thermoforming process and it was applied in this experiment. There were two types of mold had been machined which truncated semi-hemisphere mold with rectangular pocket (TSMRP) and circle pocket (TSMCP). CNC Milling Machine and EDM Wire cut were used to machined the thermoforming mold. Both of them had tested with PETG plastic sheet by using drape forming machine with constant temperature 180oC and pressure 20kpa. The data of thickness after forming process proved that the first touched of plastic sheet to the mold was produced the highest thickness while final touched had produced lowest thickness. Beside that, the when the area of deformation plastic sheet was higher, the thickness was lower.